Hubungan antara Hafalan Al-Qur’an dengan Keterampilan Berbicara Bahasa Arab Siswa Kelas VIII SMP IT Al-Huda Makassar - Isnaeni, Nurul Reski; Susiawati, Susiawati; Al-Ilmullah, Syarifah Fatimah (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This research is a correlational study using a quantitative approach that aims to determine the relationship between the memorizing the Qur'an and the Arabic-speaking skills of SMP IT Al-Huda Makassar students. The independent variable in this study was memorizing the Qur'an, while the dependent variable was the students' Arabic speaking skills. The population in this study were all 103 students of SMP IT Al-Huda Makassar, and the sample in this study were students of class VIII female students of SMP IT Al-Huda Makassar, totaling 18 people with a random sampling technique. Research data in this study were obtained by giving Al-Qur'an memorization tests and Arabic speaking skills oral tests. The data analysis technique used is the product moment correlation analysis technique, with a correlation coefficient of 0.796 and a significance value of 5.2602. The results of this study indicate that there is a strong positive relationship between Al-Qur'an memorization and the Arabic-speaking skills of SMP IT Al-Huda Makassar students. Thus, it can be concluded that there is a significant relationship between memorization of the Qur'an and the speaking skills of SMP IT Al-Huda Makassar students.